PURINE DERIVATIVE EXCRETION AND MICROBIAL PROTEIN SYNTHESIS IN SHEEP FED A ROUGHAGEBASED DIET SUPPLEMENTED WITH OR WITHOUT GRASS SILAGE. - OLUOKUN, J. A.; GREENHALGH, J.F.D.; REID, G.W. (Nigerian Journal of Animal Science, 2023)
In a 3 x 3 Latin square design experiment, urinary excretions of purine derivatives (allantoin N, Uric acid N, Xanthine + Hypoxanthine N) were measured and used to estimate microbial N yield in 9 sheep fed roughage- based diet supplemented with 0, 150 and 300g DM grass silage respectively. Daily urinary excretions of allantoin N, uric acid N, xanthine + hypoxanthine were 3.66, 3.77,4.51, 0.95,1.18,1.24; 1.01,1.21 and 1.34 mmol d-1 for sheep fed roughage-based diet and supplemented with 0,150 and 300g DM silage respectively. Allantoin N, Uric acid N and Xanthine + Hypoxanthine N excretion increased significantly (P<0.01) with increasing amount of silage. Dry matter intake which increased with level of supplementation significantly (P< 0.01) influenced estimated microbial protein yield, which ranged from 4.86 to 6.14g N d-1. The efficiency of conversion of dietary N into microbial N which ranged from 48.17 to 57.22 g N/100g DN was highly significant (P<0.01) as the level of supplementation increased. Microbial N yield per kg of OM fermented (gN/kg DOMR) increased linearly. The results indicate that the amount of microbial N biomass made available to the host animal per unit of feed fermented could be influenced by feed type, level of intake and size of animal. The results also showed that allantoin constituted the highest proportion of purine derivatives excreted.